kompetensi Prediksi Kompetensi Bagi Da'i Yang Unggul: - - Suhendar, Atep - (Decision, 2021)
This study aims to find the competencies that make the preacher successful or superior. The research method used is descriptive analytical with a qualitative approach. The sample obtained was 10 Da'i who were selected based on the opinion of the audience at the time of da'wah, given an ordinal questionnaire, namely the choice of competence. The competence chosen by the Da'i is the level of competence. Then the results of the data are processed through Cluster Analysis with Dendogram and to find or find differentiating competencies between the Superior and the ordinary Da'i, the Difference Test is carried out with Mann Whitney from SPSS. From the results of this data processing, it is found that superior preachers have distinguishing competencies, namely Innovation (Inov) level 3, Analytical Thinking (BA) level 3, and Tenacity (Keu) for level 2. Decision, Organizing, Oral Communication, and Planning are the minimum competencies that need to be possessed by both the Superior Da'i and the ordinary Da'i. The limitations of this paper are the small number of samples and the prediction of initial competence for Da'i based on observations Keyword : Da'i, Competence, Superior